Pandora's lunchbox : how processed food took over the American meal - Warner, Melanie (New York : Scribner, 2013)
From breakfast cereal to frozen pizza to nutrition bars, processed foods are a fundamental part of our diet, accounting for 65% of our nation's yearly calories. Over the past century, technology has transformed the American meal into a chemical-laden smorgasbord of manipulated food products that bear little resemblance to what our grandparents ate. Despite the growing presence of farmers' markets and organic offerings, food additives and chemical preservatives are nearly impossible to avoid, and even the most ostensibly healthy foods contain multisyllabic ingredients with nearly untraceable origins. The far-reaching implications of the industrialization of the food supply that privileges cheap, plentiful, and fast food have been well documented. They are dire. But how did we ever reach the point where 'pink slime' is an acceptable food product? Is anybody regulating what makes it into our food? What, after all, is actually safe to eat? Here the author, a former New York Times health columnist combines deep investigatory reporting, culinary history, and cultural analysis, to find out how we got here and what it is we are really eating. This book blows the lid off the largely undocumented world of processed foods and food manipulation. From the vitamin "enrichments" to our fortified cereals and bread, to the soy mixtures that bolster chicken (and often outweigh the actual chicken included), the author lays bare the dubious nutritional value and misleading labels of chemically-treated foods, as well as the potential price we, and our children, may pay.--Publisher information.
Weird science -- The crusading chemist -- The quest for eternal cheese -- Extruded and gun puffed -- Putting Humpty Dumpty back together again -- Better living through chemistry -- The joy of soy -- Extended meat -- Why chicken needs chicken flavor -- Healthy processed foods -- Sit at home and chew.
Includes bibliographical references (pages 223-245) and index.
Keywords: Food industry and trade -- United States; Processed foods -- Health aspects; Food additives -- Health aspects; SOCIAL SCIENCE -- Agriculture & Food; SOCIAL SCIENCE -- General; HEALTH & FITNESS -- Nutrition; Food additives -- Health aspects; Food industry and trade; United States; Behandeltes Lebensmittel; Lebensmittelindustrie; Zusatzstoff; USA; Food industry -- United States; Food additives -- Health aspects; HEALTH & FITNESS -- Nutrition; Processed foods -- Health aspects; SOCIAL SCIENCE -- General; SOCIAL SCIENCE -- Agriculture & Food